2015
DOI: 10.4028/www.scientific.net/kem.659.58
|View full text |Cite
|
Sign up to set email alerts
|

Composition-Microstructure-Property Relationships in BaTiO<sub>3</sub> with Mg Addition

Abstract: Rising worldwide demands for energy encourages development of high-efficiency energy storage and capacitor components. Main requirements for dielectric materials employed in fabrication of high energy density capacitors include high dielectric constant, high dielectric breakdown strength, and low dielectric loss. Owing to its high dielectric constant and low dielectric loss [1], barium titanate is among common capacitor materials. Tailoring of dielectric properties of barium titanate can be achieved through co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…01-071-2394), whose formation can be associated with a chemical reaction between barium from the initial reagent and carbon from CO 2 or the combustion fuel. Khort et al reported the formation of BaCO 3 via the reaction between barium oxide (decomposed from barium nitrate) and CO 2 , whereas Jongprateep and Tanmee observed the formation of BaCO 3 via the reaction between barium oxide and carbon from glycine [27,41].…”
Section: Phase Identification and Elemental Analysis Of Synthesized P...mentioning
confidence: 99%
“…01-071-2394), whose formation can be associated with a chemical reaction between barium from the initial reagent and carbon from CO 2 or the combustion fuel. Khort et al reported the formation of BaCO 3 via the reaction between barium oxide (decomposed from barium nitrate) and CO 2 , whereas Jongprateep and Tanmee observed the formation of BaCO 3 via the reaction between barium oxide and carbon from glycine [27,41].…”
Section: Phase Identification and Elemental Analysis Of Synthesized P...mentioning
confidence: 99%